Tunable Bandgaps: Simulation Evidence of Hexagonal‐to‐Tetragonal ZnSe Structure Transition: A Monolayer Material with a Wide‐Range Tunable Direct Bandgap (Adv. Sci. 12/2015). Issue 12 (December 2015) - Li, Lei; Li, Pengfei; Lu, Ning; Dai, Jun; Zeng, Xiao Cheng
Abstract : In article 1500290, X. C. Zeng and co‐workers demonstrate simulation evidence for a structural transition in 2D ZnSe. The 2D tetragonal ZnSe monolayer exhibits highly tunable bandgap from 2 to 3 eV under the biaxial strain, suggesting its potential application as light‐emitting material in red‐green‐blue light emission diodes or for visible‐light driven water splitting through suitable band alignment.